Death from COVID-19 in a Hispanic postpartum woman and review of the literature. Issue 7 (23rd July 2021) - Mydam, Janardhan; Younes, Laila; Siddiqui, Mohammed; Tarsha, Thana
Abstract : There is still much we do not know about the impact of COVID-19 on the health of pregnant and postpartum women and pregnancy outcomes. Current evidence suggests that there is biological plausibility for worse outcomes among this population. This case report details the clinical care given to a postpartum Hispanic and obese woman diagnosed with COVID-19 in April 2020. We report the care she and her newborn received and her progression through the virus. We discuss the current knowledge surrounding COVID-19 among pregnant and postpartum women. While research supports COVID-19 outcomes being comparable to the general population, there is limited research in this area. Clinical trials, acting on the side of caution, have tended to exclude pregnant women from participation. Therefore, there is a need for further research that can inform evidence-based policy decisions related to COVID-19 in pregnant and postpartum women.